2006
DOI: 10.1002/eat.20261
|View full text |Cite
|
Sign up to set email alerts
|

Anorexia nervosa in young men: A cohort study

Abstract: Male gender in AN--on a group level--suggests a good psychiatric prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Most studies on therapy have been conducted in males with Anorexia Nervosa (AN) undergoing inpatient-residential treatment. A Swedish case register study (n ¼ 61) (Lindblad et al, 2006) for example found that the outcome of males with AN admitted for hospital treatment was better than for females which is in agreement with the findings of Strober et al (2006). Also, Deter et al (1998) reported a better psychosocial outcome in men with AN than in women, albeit two male cases died in this cohort.…”
Section: Therapy For Anorexia Nervosa Malessupporting
confidence: 76%
See 1 more Smart Citation
“…Most studies on therapy have been conducted in males with Anorexia Nervosa (AN) undergoing inpatient-residential treatment. A Swedish case register study (n ¼ 61) (Lindblad et al, 2006) for example found that the outcome of males with AN admitted for hospital treatment was better than for females which is in agreement with the findings of Strober et al (2006). Also, Deter et al (1998) reported a better psychosocial outcome in men with AN than in women, albeit two male cases died in this cohort.…”
Section: Therapy For Anorexia Nervosa Malessupporting
confidence: 76%
“…Other studies have however referred to a better (Deter, Kopp, Zipfel, & Herzog, 1998;Lindblad, Lindberg, & Hjern, 2006;Strober et al, 2006) or even a poorer (Oyebode, Boodhoo, & Schapira, 1988) outcome in male patients when compared to females of the same ED diagnosis.…”
Section: Outcome Of Eds Across Gendermentioning
confidence: 97%
“…The mortality rate associated with ED is high; for example, AN has the highest mortality rate of any psychiatric disorder [1], although recent studies indicate a trend towards a decrease in rate (e.g., [2]), likely mirroring earlier detection and improved care of these patients. Suicide attempts are also frequent; in fact, Damstedt, Petersen, Bilenberg and Hörder [3] found suicidal behavior in 40% of adolescents with ED.…”
Section: Introductionmentioning
confidence: 99%
“…In 2009, approximately 6 children were born per 1,000 young women aged [15][16][17][18][19], and the birth rate has remained unchanged for the past five years after a long decline over many years. …”
Section: Sexual and Reproductive Health Among Young Peoplementioning
confidence: 99%